Penerapan Aplikasi Supply Chain Management (SCM) Untuk Pendistribusian dan Stock Kerupuk Jangek “Nila” Berbasis Web - Dinul Akhiyar; Radiyan Rahim (Riset Sinergi Indonesia (RISINDO), 2022)
Supply Chain Management (SCM) is the activity stream of goods that includes planning, providing, production, storage, taransportasi, and distribution of, ranging from the initial point of raw materials (upstream) to the point of usage (downstream). The purpose of this paper is to provide knowledge on supply chain management as well as the components contained within the supply chain management, and implementation of the company is the effort karupuak jangek mintu, in helping the company's operations daily. Starting from the supply of raw materials to finished products (karupuak jangek), and activities relating to the distribution of products karupuak jangek up to the consumer. So that the necessary supply chain management to support and coordinate all of these requirements